2013
DOI: 10.1021/ja4078864
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Directable Electron Transfer Reactions. Dramatic Rate Enhancement in the Chemoselective Reduction of Cyclic Esters Using SmI2–H2O: Mechanism, Scope, and Synthetic Utility

Abstract: Substrate-directable reactions play a pivotal role in organic synthesis, but are uncommon in reactions proceeding via radical mechanisms. Herein, we provide experimental evidence showing dramatic rate acceleration in the Sm(II)-mediated reduction of cyclic esters that is enabled by transient chelation between a directing group and the lanthanide center. This process allows unprecedented chemoselectivity in the reduction of cyclic esters using SmI2-H2O and for the first time proceeds with a broad substrate scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 60 publications
4
38
0
Order By: Relevance
“…These two substituents differ from the others by two features. The first is that these two substituents are capable of delocalizing the negative charge from the benzylic position onto themselves, and the second is that they are capable of binding to the samarium cation 10a. 25 Although it is unlikely that the electron‐withdrawing power of the p ‐CN and p ‐CO 2 Me substituents alone is sufficient to overcome the electronegativity of Cl and Br, their pairing with the triply charged samarium cation, apparently results in more efficient negative charge stabilization on the benzylic fragment than by its localization on the nucleofuge.…”
Section: Resultsmentioning
confidence: 99%
“…These two substituents differ from the others by two features. The first is that these two substituents are capable of delocalizing the negative charge from the benzylic position onto themselves, and the second is that they are capable of binding to the samarium cation 10a. 25 Although it is unlikely that the electron‐withdrawing power of the p ‐CN and p ‐CO 2 Me substituents alone is sufficient to overcome the electronegativity of Cl and Br, their pairing with the triply charged samarium cation, apparently results in more efficient negative charge stabilization on the benzylic fragment than by its localization on the nucleofuge.…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, only alcohol products were formed, suggesting that chelation does not override the inherent reaction pathway. 16 We also found that amides featuring substituents known to afford mixtures of C–N/C–O cleavage products with other reagents 2a were amenable to the Sm(II) reduction protocol and that useful levels of chemoselectivity were obtained with these substrates (entries 13 and 14). We note, however, that N , N -diisopropylamide was unreactive under our reaction conditions (entry 15).…”
mentioning
confidence: 79%
“…[16] The positioningo fa na lkene tether at the apositiontothe carbonyl group in a1,3-arrangement with achelating substituent enabled efficient reductive cyclization by adirecting group mechanism. [17] Mechanistically,t he cyclization proceeds by electron-transferr eduction of the imide carbonyl to generate an electron-rich aminoketyl radical, [18] which added to the p acceptor (cf. reduction of the acceptora nd anionic addition).…”
mentioning
confidence: 99%
“…[22] To our knowledge this result represents ar are example of aS mI 2 -induced cyclization of an N-tethered unactivated olefin. [2a] With optimized conditions in hand, the scope of the reaction was next explored.S pecifically,t he examples were selected to cover the range of functional group tolerance with the highly discriminating SmI 2 /H 2 Or eagent [2l] and comparet he directing group effect [17] on the cyclization efficiency ( Table 2). As shown, the method readily accommodates ar ange of functional groups reductively removed with other lanthanide reagents, [1,2] including ethers (entry 2), benzyl fluorides (entry 3), aryl bromides (entry 4), naphthalenes (entry 5), and heterocycles (entry 6).…”
mentioning
confidence: 99%